Interactions : collaboration skills for school professionals - Friend, Marilyn; Cook, Lynne (Upper Saddle River, NJ : Pearson Education, 2013)
Gives readers essential skills for working collaboratively and effectively with colleagues, administrators, professionals, parents, and families toward quality education for all students.
1. Foundations and perspectives -- 2. Interpersonal communication -- 3. Listening, responding and giving feedback -- 4. Integrating skills in interviews -- 5. Interpersonal problem solving -- 6. Teams -- 7. Co-teaching -- 8 .Consultation, coaching and mentoring -- 9. Difficult interactions -- 10. Paraeducators -- 11. Families -- 12. Community and interagency contexts -- 13. Issues related to education collaboration.
Includes bibliographical references and index.
Keywords: COMMUNICATION IN EDUCATION; INTERPERSONAL RELATIONS; TEACHING TEAMS; SPECIAL EDUCATION TEACHERS -- TRAINING OF